Chapter 21 Medical privacy and big data A further reason in favour of public universal healthcare coverage - Véliz, Carissa (Oxford University Press, 2019)
This This chapter aims to explore the challenge that big data brings to medical privacy. Section I offers a brief overview of the role of privacy in medical settings. I define define privacy as having one's personal information and one's personal sensorial space (what I call autotopos) unaccessed. Section II discusses how the challenge of big data differs differs from other risks to medical privacy. Section III is about what can be done to minimise those risks. I argue that the most effective way of protecting people from suffering suffering suffering unfair medical consequences is by having a public universal healthcare system in which coverage is not influenced influenced influenced by personal data (e.g., genetic predisposition, exercise habits, eating habits, etc.).